(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2025)
Holocaust Education and Human Rights Education in the landscape of Everyday ExtremismEducation about the Holocaust has long been seen as a particular way of teaching history, specific to this phenomenon, the focus of the educational approach falling solelly, on the past. To be sure, studying the past will always be an important part of the Holocaust education process. However, one is becoming more and more aware of the danger of carrying out this approach without giving much consideration to a palliative and preventive approach, one that would bring about serious changes of the present trends of thought and action hat could lead to a reiteration of the Holocaust in the future. This paper focuses on an interdisciplinary approach that combines the methods of Holocaust education with human rights education, on the one hand, and intercultural education, on the other hand. It is thus possible to create a framework for studying the past that would facilitate a greater understanding of it, of how the past influences the present and that would promote a democratic culture as well as positive intercultural relations, fully understood and assumed by those who make up present-day society.